Air-coupled impact-echo damage detection in reinforced concrete using wavelet transforms. (30th December 2016) - Epp, Tyler; Cha, Young-Jin
Abstract: Internal damage detection of reinforced concrete (RC) structures is a challenging field that has garnered increasing attention over the past decades due to a decline in the state of infrastructure in North America. As a nondestructive testing mode, the impact-echo method is currently a promising approach. However, it requires intensive testing to cover large-scale civil RC structures with point-by-point inspection. In order to partially overcome this limitation, this study proposes a new impact-echo analysis method using wavelet transforms with dual microphones with 20 kHz resolution to improve damage detection capability. The signals recorded from the microphones are processed to recover spectral data that are further analyzed using percentage of energy information to determine the condition of the specimen and detect in situ damages. In order to validate the performance of the proposed method, the results from traditional signal processing using FFT and wavelet transforms are compared. The proposed wavelet transform based approach showed better accuracy when covering broader areas, which can contribute to reduce testing time significantly when monitoring large-scale civil RC structures.